Changes in soil carbon, nitrogen, and phosphorus in Pinus massoniana forest along altitudinal gradients of subtropical karst mountains - Kun Nie; Ming Xu; Jian Zhang (PeerJ, 2023)
Changes in altitude have a long-term and profound impact on mountain forest ecosystems. However, there have been few reports on changes in soil carbon, nitrogen, and phosphorus contents (SCNPC) along altitudinal gradients in subtropical karst mountain forests, as well as on the factors influencing such changes. We selected five Pinus massoniana forests with an altitudinal gradient in the karst mountain area of Southwest China as research objects and analyzed the changes in SCNPC along the altitudinal gradient, as well as the influencing factors behind these changes. Soil organic carbon, total nitrogen, and available nitrogen contents first increased and then decreased with increasing altitude, whereas the contents of total phosphorus and available phosphorus showed no obvious trend. In the karst mountain P. massoniana forest, SCNPC in the topsoil is most significantly affected by total glomalin-related soil protein (TG) and soil moisture content (SMC) (cumulative explanatory rate was 45.28–77.33%), indicating that TG and SMC are important factors that affect SCNPC in the karst mountain P. massoniana forest. In addition, the main environmental factors that affect SCNPC in the subsoil showed significant differences. These results may provide a better scientific reference for the sustainable management of the subtropical mountain P. massoniana forest.